Determinants of surgical decision making: a national survey - Wilson, Niamey P. (2013)
BACKGROUND: We conducted a national survey of general surgeons to address the association between surgeon characteristics and the tendency to recommend surgery. METHODS: We used a web-based survey with 25 hypothetical clinical scenarios with clinical equipoise regarding the decision to operate. The respondent-level tendency to operate (TTO) score was calculated as the average score over the 25 scenarios. Surgical volume was based on self-report. Linear regression models were used to evaluate the associations between TTO, other covariates of interest, and surgical volume. RESULTS: There were 907 respondents. The mean surgical TTO was 3.05 ± .43. Surgeons had significantly lower TTO scores when responding to questions within their area of practice (P < .0001). There was no association between TTO and malpractice concerns, financial incentives, or compensation structure. CONCLUSIONS: Surgeons recommend intervention far less frequently within their area of specialization. Malpractice concerns, volume, and financial compensation do not significantly affect surgical decision making.